Cell collectivity regulation within migrating cell cluster during Kupffer's vesicle formation in zebrafish - Matsui, Takaaki; Ishikawa, Hiroshi; Bessho, Yasumasa (Frontiers in Cell and Developmental Biology, 2015)
Although cell adhesion is thought to fasten cells tightly, cells that adhere to each other can migrate directionally. This group behavior, called “collective cell migration”, is observed during normal development, wound healing, and cancer invasion. Loss-of-function of cell adhesion molecules in several model systems of collective cell migration results in delay or inhibition of migration of cell groups but does not lead to dissociation of the cell groups, suggesting that mechanisms of cells staying assembled as a single cell cluster, termed as “cell collectivity”, remain largely unknown. During the formation of Kupffer’s vesicle (KV, an organ of laterality in zebrafish), KV progenitors form a cluster and migrate together toward the vegetal pole. Importantly, in this model system of collective cell migration, knockdown of cell adhesion molecules or signal components leads to failure of cell collectivity. In this review, we summarize recent findings in cell collectivity regulation during collective migration of KV progenitor cells and describe our current understanding of how cell collectivity is regulated during collective cell migration.